Risk Factors Increasing Prevalence of Type 2 Diabetes Under The Age of 40 Years Attending Al-Diwanyia Teaching Hospital - Hassan Raji Jallab1, Zahraa Abdul Ameer Kadhim1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The present case control study of Iraqi people living in Aldiwanyia city to identify the attributable risk factors that leads to type 2 diabetes in younger age groups and the correlation of the most prevalence risk for developing diabetes. The study was designed to be a case control study includes 315 individuals, 150 is the number of controls, and the rest of the participants are patients that have been diagnosed by diabetes mellitus type 2 before or at age of 40 years .All these participants attended outpatient clinics at Al- Aldiwanyia teaching hospital in Al-Dewaniyah province/ Iraq. The beginning of data collection was dated on the January 2019 and ended on June 2019. Mean age of patients with diabetes mellitus was significantly higher than that of control subjects There was highly significant difference in the frequency distribution according to marital status, occupation, residency, level of education,economic status in patients and controls groups .It appears that the rate of overweight and obesity is comparable in patient and control group.